Investigation of Sustainable Housing Criteria - Nurakmal, Abdullah@ Goh Tuo Ho; Roshanfekr, Somayeh; Norngainy, Mohd Tawil (EDP Sciences, 2016)
Recently, much attention has been paid to sustainable development in cities. The quality of human life is directly related to environmental quality. Because many people live in cities as a place of social, economic and cultural relationships, certain issues such as environmental crises, energy, air and noise pollution and traffic jams are some of the factors that can alter the quality of human life. Therefore, in order to improve the quality of human life, attention to sustainable development (or sustainability) in cities is proposed. Sustainable building has a comprehensive significance that begins with the conception of negative and positive impacts on the environment. Several descriptions of sustainable or green buildings have been created; however, they all pursue one goal, which is to create sustainable urban developments and protection of the environment. The quality of indoor environments, materials, and energy consumption, water usage, the impact of building construction processes and building maintenance are some of the factors that affect the environment and sustainability. Sustainable building is an attempt to relieve the minus impacts on the environment that occur during a building’s lifetime. This research investigates the important factors that have relevance to green buildings and introduces several criteria of sustainable housing.